15-(3-4y)=(y+2)

Simple and best practice solution for 15-(3-4y)=(y+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15-(3-4y)=(y+2) equation:


Simplifying
15 + -1(3 + -4y) = (y + 2)
15 + (3 * -1 + -4y * -1) = (y + 2)
15 + (-3 + 4y) = (y + 2)

Combine like terms: 15 + -3 = 12
12 + 4y = (y + 2)

Reorder the terms:
12 + 4y = (2 + y)

Remove parenthesis around (2 + y)
12 + 4y = 2 + y

Solving
12 + 4y = 2 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
12 + 4y + -1y = 2 + y + -1y

Combine like terms: 4y + -1y = 3y
12 + 3y = 2 + y + -1y

Combine like terms: y + -1y = 0
12 + 3y = 2 + 0
12 + 3y = 2

Add '-12' to each side of the equation.
12 + -12 + 3y = 2 + -12

Combine like terms: 12 + -12 = 0
0 + 3y = 2 + -12
3y = 2 + -12

Combine like terms: 2 + -12 = -10
3y = -10

Divide each side by '3'.
y = -3.333333333

Simplifying
y = -3.333333333

See similar equations:

| 2y^3+7=0 | | 7/n-1=9/n+1 | | -10x+62=-6x+34 | | 4x^2+43x+70=0 | | 5/n+1=6/n+5 | | x=.3x+8 | | .18x+16=4+.54x | | 3x^2-4x+7=x^2+15x | | 6/2=p-6/p-2 | | 9/m+3=2/4 | | 0=4x^4-18x^3+34x^2-72x+72 | | -28-(-130)= | | 8-7n+5n=44-86 | | 1.5(b+2)+15(2b-9)+b=90 | | 8x+6x-88=66-8x | | 6x=9x-5 | | 10/5=6/k-9 | | 27+w=35 | | -4z^2+6z+1=0 | | 3x(x-6)=6x-90 | | -12x+14=-6x+8 | | 4/2=x/7 | | 9(c-4)+5=3+c-34 | | m/8=10/2 | | 4y=x^2+4x | | -9=-8(1+6y)-1 | | 8f=7f+-3 | | 3/6=p-6/p-4 | | (10x-9)-(-x^2+22x)= | | -3x^2=8-10x | | 12(a-9)=-7-5 | | 3lnx-2ln(5-x)=0 |

Equations solver categories